A test of common content knowledge for gymnastics: A Rasch analysis - (:unkn) unknown (SAGE PUBLICATIONS LTD, 2019)
Common content knowledge (CCK) is comprised of the knowledge of rules, techniques, and tactics and can be used to define the scope of what teachers teach in their lessons. Developing reliable and valid measures of teacher knowledge such as CCK strengthens our understanding of what teachers know and in turn the field's ability to help teachers in their practice. There are, however, few validated tests of CCK of sport for teachers. The primary purpose of this study was to provide content and concurrent validity evidence for a 19-question test of the CCK for gymnastics required in Turkish elementary and secondary schools. Participants were 240 preservice teachers who had previously taken a class in content knowledge for gymnastics in six state universities. Rasch modeling was used to evaluate the validity and reliability of the CCK gymnastics test. Results indicated good item model fit for all 19 items. High internal consistency for item difficulty and high internal consistency for person-ability were obtained. Overall analysis showed good evidence to support the validity and reliability of the CCK gymnastics test. The CCK test can be used in initial teacher education and continuing professional development to determine the CCK knowledge of preservice and inservice teachers and in turn a measure of what they learn from professional development efforts.
Keywords: Professional development; teacher education; Physical Education; teaching; HEALTH-RELATED FITNESS; CONCEPTIONS